Brown rats (Rattus norvegicus) as potential reservoirs of Enterocytozoon bieneusi in Heilongjiang Province, China: high prevalence, genetic heterogeneity, and potential risk for zoonotic transmission - Jiang, Yanyan; Zhou, Shanshan; Yuan, Zhongying; Hu, Xinyu; Li, Zhen; Wang, Yaxue; Shen, Yujuan; Cao, Jianping (Frontiers in Veterinary Science, 2024)
Introduction Enterocytozoon bieneusi, an obligatory intracellular fungus, is prevalent among animals and humans. Due to their close interaction with humans and their extensive regional distribution, brown rats (Rattus norvegicus) are important pathogen reservoirs. To assess the zoonotic transmission potential of E. bieneusi, a molecular investigation was conducted on 817 R. norvegicus from four cities in Heilongjiang Province, China. Methods A total of 817 R. norvegicus were collected from four cities in Heilongjiang Province, China. The genotyping of E. bieneusi was conducted through PCR amplification of the small subunit ribosomal RNA (SSU rRNA)’s internal transcribed spacer (ITS) segments. Phylogenetic and similarity analyses were used to examine zoonotic potential and genetic characteristics of the E. bieneusi-positive specimens. Results Among the 817 R. norvegicus, the total infection rate was 33.3% (272/817). Seventy-five genotypes were identified, including 14 known genotypes D (n = 167), A (n = 15), HLJ-CP1 (n = 12), WR8 (n = 6), EbpC (n = 2), BEB6 (n = 1), CS-4 (n = 1), CHPM1 (n = 1), Henan-II (n = 1), HNH-22 (n = 1), HNH-25 (n = 1), I (n = 1), JLD-XI (n = 1), SDD5 (n = 1), and 61 novel genotypes designated as SHWR1 (n = 10), SYSWR1 (n = 2), and SHWR2 to SHWR17, SYSWR2 to SYSWR36 and QTHWR1 to QTHWR8 (n = 1, each). Moreover, 10 samples exhibited mixed genotype infections, including D + A (n = 3), D + EbpC (n = 1), D + HLJ-CP1 (n = 1), D + SHWR1 (n = 1), D + SHWR16 (n = 1), D + SHWR17 (n = 1), SDD5 + WR8 (n = 1), and CS-4 + SYSWR36 (n = 1). Phylogenetic analysis grouped the genotypes into three main groups: group 1 (n = 67), group 2 (n = 5), and group 9 (n = 3). Discussion The high prevalence and genetic diversity of E. bieneusi in Heilongjiang Province’s R. norvegicus imply that these animals spread the pathogen. The R. norvegicus that E. bieneusi carries can spread zoonotic disease, making it a serious hazard to the local human population. Therefore, it is imperative to raise awareness about the dangers posed by R. norvegicus and implement measures to reduce their population to prevent environmental contamination.